All work and no play? Autonomous vehicles and non-commuting journeys. Issue 4 (4th July 2021) - Thomopoulos, Nikolas; Cohen, Scott; Hopkins, Debbie; Siegel, Lauren; Kimber, Simon
ABSTRACT: People travel by car for a wide variety of reasons. A large proportion of household travel is for non-commuting purposes, including social and recreational journeys. The emergence and (potential) diffusion of highly automated vehicles, also known as autonomous vehicles (AVs), could transform the way (some) people work and travel. Should they become mainstream, AVs could reshape patterns of leisure travel. To date, however, the impacts and implications of AVs beyond commuting trips have received minimal attention from transport scholarship. This paper presents a state-of-the-art review of literatures on AVs. It follows PRISMA guidelines and synthesises 63 papers on AV travel focusing on non-commuting journeys, including travel for purposes of leisure, tourism, shopping and visiting friends and relatives. Given the economic importance of the tourism sector and its inherent focus on non-commuting journeys, this analysis is supplemented with a review of the extent to which national tourism strategies of countries leading AV deployment include reference to AVs. The paper reveals an overwhelming focus on commuting journeys in existing AV studies as less than one-fifth of the reviewed academic sources include non-commuting as part of their wider analysis. The review's further key findings are that the interest of publics in AVs for leisure journeys appears to exceed that for commuting, sharing vehicles will be less likely when AVs are used for leisure and there is an absence of recognition in the literature that certain non-commuting journeys will require a lower SAE level of automation. Surprisingly, analysis of the national tourism strategies of countries most prepared to meet the challenges of AVs shows that just three countries make specific reference to AVs within their national tourism strategies. The paper contributes to setting future AV policy agendas by concluding that two gaps must be narrowed: one, the distance between how academic studies predominantly conceive of AV use (commuting) and articulated public interest in AVs for non-commuting journeys; and two, the lack of readiness in certain national tourism strategies to accommodate AVs. As non-commuting journeys are likely to represent some of the earliest trip purposes for which AVs could be adopted, the paper points to the potential barriers to AV uptake by remaining focused on a limited set of trip purposes.